Social information use increases with decreasing winter temperature in a passerine bird - Emil Isaksson; Jan J. Wijmenga; Alexis Chaine; Roslyn Dakin; Julien G. A. Martin; Kimberley J. Mathot (Royal Society Open Science)
Foragers can gain knowledge of profitable foraging opportunities either by sampling the environment directly (asocial information) or from congeners (social information). The relative benefit of using social information over asocial information is context-specific, and social information use is expected to be particularly beneficial when the costs of acquiring asocial information are high, for example, due to high risk of starvation if asocial information fails. We investigated the plasticity of social information use in an overwintering population of black-capped chickadees (Poecile atricapillus) as they rediscovered an intermittently available food source. Lower temperatures impose energetic costs that increase the risk of starvation in chickadees; therefore, lower temperatures are predicted to favour higher use of social information. To test this prediction, we evaluated chickadees’ reliance on social information during foraging as ambient temperatures ranged from −11.0°C to 5.5°C. We evaluated the relative strength of reliance on social and asocial information using network-based diffusion analysis. We found increased reliance on social information transmission with decreasing temperature. Reversible plasticity of social information use may be an important mechanism to cope with low ambient temperatures, a seasonal challenge experienced by many animals.